Step 1
write out the general formula of an exponential is
![y=ab^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/hye5rg1h8wj3ohgdt4j1vpepdhoym0w9ex.png)
1) Thus for the first equation
![\begin{gathered} y=3^x \\ a=1 \\ b=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dg3nqzv40g2tsh9o5xsk7i4do14xhmo0tn.png)
For the second equation
![\begin{gathered} y=-3^x \\ a=-1 \\ b=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zw7mt60u9adbbm903b3d4r86uy3pgpufz9.png)
2) For the equation
![\begin{gathered} y=3^x \\ \text{The y-intercept is 1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/46c2vdm059wzybq3ekofuww8wbfpfgncq3.png)
For the equation
![\begin{gathered} y=-3^x \\ \text{the y-intercept is -1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d9ur9hg27zs021nkcqnaoqiu742wfhd8hf.png)
3) For equation
![\begin{gathered} y=3^x \\ \text{The values y remains constant for a range of x and increases exponentially with further increase in the value of x } \end{gathered}]()
For equation
![y=-3^x](https://img.qammunity.org/2023/formulas/mathematics/college/2ixym91qftwk62898ghnu7d3yf8da7vj0t.png)
The values of y remain constant for a range of x values and decrease exponentially with further increase of x values